FREQUENCY OF ANAEMIA AND RENAL INSUFFICIENCY IN PATIENTS WITH HEART FAILURE - Khan, Muhammad; Jehangir, Waqas; Daood, Muhammad Salman; Khan, Ahmad; Mallick, Nadeem Hayat (Journal of Ayub Medical College Abbottabad, 2010)
Background: Heart Failure (HF) is a common disease with a high mortality rate. Anaemia and renal failure (RF) are often present in patients with HF and associated with worse prognosis. Objective of study was to evaluate the prevalence of anaemia and RF in patients with HF. Methods: Patients admitted in Punjab institute of cardiology Lahore with diagnosis of heart failure were enrolled from February, 2008 to December, 2008. Anaemia was defined as haemoglobin levels <13 mg/dl for men and 12 mg/dl for women. Renal function was assessed by the glomerular filtration rate (GFR), calculated by the simplified formula of the MDRD (Modification of Diet in Renal Disease) study. Results: Of the 276 patients included in this study, 42.03% (116) had anaemia and 38.40% (106) had moderate to severe renal failure (GFR <60 ml/min). Conclusion: The prevalence of anaemia and renal failure was high in this population and was associated with the severity of the HF (functional classes III and IV). Keywords: Heart failure, anaemia, renal insufficiency